THE HISTORICAL ROLE OF THE SCOUT MOVEMENT IN ISLAMIC EDUCATION - Ersa Nabilla Sufi; Salwa Ramadani; Yulinda Ritonga (Journal of Educational Science Learning and Research, 2024)
The aim of this research is to identify The historical role of scouts towards Islamic Education The approach used in this research is a qualitative descriptive approach, observation, interview and documentation methods. The research results can be explained. The research results show that (1) role history of scouting towards Islamic educational institutions has a contribution scout activities, scouts have experienced developments in terms of the role and function of the organization, such as the historical appointment of scouts to Islamic educational institutions, unfortunately they have certification in providing a constructive contribution to better Islamic educational institutions in terms of teaching quality or anything extracurricular